A capillary flow-driven microfluidic device for point-of-care blood plasma separation - Brakewood, William; Lee, Kiara; Schneider, Lindsay; Lawandy, Nabil; Tripathi, Anubhav (Frontiers in Lab on a Chip Technologies, 2022)
Plasma has significant utility as an input for diagnostics and screening for conditions such as viral infections, cancer, and more. However, plasma is difficult to obtain at the point-of-care, as separation from whole blood is typically carried out via centrifugation. We have designed and optimized a low-cost, simple-to-operate microfluidic device which carries out the separation of plasma from whole blood. The device utilizes depth filtration as its separation mechanism and collects plasma via capillary action, allowing for operation without components that drive flow externally. We first optimized device dimensions and operating parameters and demonstrated consistent separation efficiencies for the samples with hematocrits ranging from 25–65%. The impact of input sample hematocrit percentage on flow rate through the device was also examined, with samples with hematocrits greater than 45% decreasing plasma flow rate. Lastly, we evaluated the ability of this device to produce plasma with a high protein concentration and found no significant difference between protein levels in samples from the device compared to samples produced via centrifugation. This system produced plasma with a maximum separation efficiency of 88.5% and achieved a maximum plasma volume of ∼14 μl from a 50 μl whole blood input. The low cost, simplicity of operation, and high plasma quality associated with this device give it many advantages in a point-of-care setting. This device could be integrated into plasma-based diagnostic workflows to increase access to various types of disease testing and monitoring.